PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EVERYONE IS A TEACHER HERE BERBANTUAN MEDIA QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X IPS SMA LABORATORIUM UNIVERSITAS SYIAH KUALA - Thohirah, Afifah; Abdi, Abdul Wahab; Jummi, Cut Vita Rajiatul (Universitas Syiah Kuala, 2024)
The Everyone is a Teacher Here learning model is a cooperative approach designed to enhance students understanding actively and enjoyably, in line with competency demands. This study aims to analyze the improvement in student learning outcomes, teacher and student activities, teacher skills in managing learning, and student responses to this model. The research employs a quantitative approach in the form of classroom action research (CAR). The subjects were 30 Class X IPS students at the Laboratory High School, Syiah Kuala University. Data were collected through tests, observations, and questionnaires and analyzed using descriptive percentage statistics. The results indicate significant improvements in various aspects. Individual mastery increased from 40% (Cycle I) to 70% (Cycle II) and 93% (Cycle III), while classical mastery rose from 30% to 60% and 90%, respectively. Teacher and student activities also improved, from 70% (Cycle I) to 100% (Cycle III). Teacher skills in managing learning increased from moderate (score 2.26) in Cycle I to very good (score 3.83) in Cycle III. Additionally, 92% of students reported that this model enhanced their understanding, motivation, and enjoyment of learning.Thus, the Everyone is a Teacher Here model, supported by Quizizz Media, has proven effective in improving Geography learning outcomes among Class X IPS students at the Laboratory High School, Syiah Kuala University, while also increasing student engagement, teaching effectiveness, and creating a more interactive and enjoyable learning experience.